Filament winding of fiber reinforced thermoplastic polymer composites - Ng, Jia Hui (Nanyang Technological University, 2020)
The growing threat of global warming has caused the world to place more importance on material recyclability. Due to their ability to reform under high temperature and pressure, as well as their remarkable mechanical properties, thermoplastic composites have become an attractive solution for manufacturers to tackle this issue. The aim of this study was to determine an optimal sample fabrication procedure for a filament-wound fiber reinforced thermoplastic polymer composite structure. The effects of pressure used in this fabrication method on the quality of the structure produced were also explored. The quality of the sample produced was assessed based on its porosity level, lateral compressive strength, as well as the degree of crystallinity of the polymer present in the matrix. The results showed that a closed compression molding process is the most appropriate sample fabrication process to produce quality filament-wound composites containing glass fibers and polyamide-6 (PA6) matrix. The porosity of the glass-PA6 sample was found to be inversely related to the pressure applied in the fabrication process, while the flexural rigidity and the degree of crystallinity of the sample are optimal at 1.5MPa and 1MPa pressure, respectively. These results provide a guideline for manufacturers to select a suitable pressure level for adopting closed compression molding based on their needs. The introduction of alternative heat treatment procedures, as well as new quality evaluation methods, were some of the recommendations made that could potentially improve the usefulness of this study.